2019
DOI: 10.1002/bdr2.1535
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mesenchymal stem cells on doxorubicin‐induced testicular toxicity and progeny outcome of male prepubertal rats

Abstract: Background: Many therapies to treat cancer are gonadotoxic and can lead to infertility. New strategies to diminish the side effects and protective plans during and after chemotherapy are needed. Therefore, bone marrow mesenchymal stem cells (BM-MSCs) as a novel solution were investigated against doxorubicin (Dox)-induced toxicity in rat testes. Methods: Forty male albino prepubertal rats were divided into four groups, 10 rats per each group. The first was injected intraperitoneally with saline as control. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 49 publications
(62 reference statements)
2
12
0
Order By: Relevance
“…Different strategies have been used to ameliorate the adverse effects of CP, including its combination with other drugs, either chemical or natural products [6,7]. However, recent advances in regenerative medicine have focused on mesenchymal stem cells (MSCs) as a therapeutic option for various types of organ toxicity induced by chemotherapy [8][9][10][11] as well as different models of brain injury [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Different strategies have been used to ameliorate the adverse effects of CP, including its combination with other drugs, either chemical or natural products [6,7]. However, recent advances in regenerative medicine have focused on mesenchymal stem cells (MSCs) as a therapeutic option for various types of organ toxicity induced by chemotherapy [8][9][10][11] as well as different models of brain injury [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Abdelaziz et al (2019) revealed that MDA levels, which are indicators of lipid peroxidation, were increased in DOX-induced testicular toxicity and there was decreased total antioxidant capacity Cabral et al (2018). showed that MDA levels in the DOX group were significantly increased in DOX-induced testicular dysfunction in rats Benzer et al (2018).…”
mentioning
confidence: 98%
“…Morphologically, testicular atrophy due to Dox, diameter of seminiferous tubules and germinative cell layer thickness were significantly reduced after BM-MSC transplantation. BM-MSCs were effective in restoring the structural efficiency of the reproductive system in testicular injury [44].…”
Section: Application Of Msc In Testicular Damage -In Vivo Experimentsmentioning
confidence: 97%